Importation of SARS-CoV-2 Omicron variant in Beijing, China - Fu Li; Zhichao Liang; Shujuan Cui; Bing Lv; Zhaomin Feng; Hui Xu; Lei Jia; Peng Yang; Quanyi Wang; Yang Pan; Daitao Zhang (Elsevier, 2022)
Omicron (B.1.1.529), the fifth variant of concern (VOC) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was firstly identified in November 2021 in South Africa. Omicron contains far more genome mutations than any other VOCs ever found, raising significant concerns about its increased transmissibility and immune evasion. Here, we report the importation of the Omicron variant into Beijing, China, in December 2021. Full-length genome sequences of five imported strains were obtained, with their genetic features characterized. Each strain contained 57 to 61 nucleotide substitutions, 39 deletions, and 9 insertions in the genome. Thirty to thirty-two amino acid changes were found in the spike proteins of the five strains. The phylogenetic tree constructed by the maximum likelihood method showed that all five imported genomes belonged to Omicron (BA.1) (alias of B.1.1.529.1), which is leading to the current surge of coronavirus disease 2019 (COVID-19) cases worldwide. The globally increased COVID-19 cases driven by the Omicron variant pose a significant challenge to disease prevention and control in China. Continuous viral genetic surveillance and increased testing among international travellers are required to contain this highly contagious variant.